Conducting and reading research in health and human performance - Baumgartner, Ted A.; Hensley, Larry D. (Larry Duncan), 1948- (Boston, Mass. : McGraw-Hill, 2006)
Designed for the first course in research methods, this text shows students how to conduct and read research, design research tools, and evaluate results in health, kinesiology, exercise science, recreation, dance, and all other areas of human performance--providing comprehensive coverage of both quantitative and qualitative research methods.
rt I The Research Process 1 The Nature and Purpose of Research -- 2 The Research Problem -- 3 Searching the Literature -- 4 Developing the Research Plan -- 5 Ethical Concerns in Research -- 6 Selection of Research Participants: Sampling Procedures -- 7 Reading and Evaluating Research Reports -- Part II Types of Research -- 8 Experimental Research -- 9 Descriptive Research -- 10 Qualitative Research -- 11 Meta-Analysis -- 12 Additional Research Approaches -- Part III Data Analysis -- 13 Descriptive Data Analysis -- 14 Inferential Data Analysis -- 15 Measurement in Research -- Part IV The Research Report -- 16 Developing the Research Proposal -- 17 Writing the Research Report
Includes bibliographical references and index.
1
Keywords: Medicine -- Research -- Methodology; Health -- Research -- Methodology